Visual Outcome after Cataract Surgery in Phacomorphic Glaucoma in Tertiary Eye Care Centre in Western Nepal - Devkota, Prabhat Kiran; Khattri Chattri, Shital; Yogi, Anita; Pokhrel, Sushila; Khadka Thapa, Saraswati (Journal of Bharatpur Hospital, 2025)
Background Phacomorphic glaucoma is a preventable secondary glaucoma resulting from neglected cataract. This study evaluated the visual and intraocular pressure (IOP) outcomes after cataract surgery in patients diagnosed with phacomorphic glaucoma. Methods A prospective observational study was conducted at Lumbini Eye Institute, Bhairahawa, Nepal, from August 1 to September 15, 2025, including 42 patients with phacomorphic glaucoma. All underwent comprehensive ophthalmic evaluation and manual small incision cataract surgery (SICS) with intraocular lens implantation. Pre- and postoperative visual acuity (VA), IOP, and complications were assessed. Statistical analyses were performed using SPSS version 16, with significance set at p-value<0.05. Results The mean age was 57.9±10.05 years, with a male-to-female ratio of 1:1.2. Most patients were farmers (69%) from lower socioeconomic backgrounds. The median VA improved significantly from 2.7 LogMAR preoperatively to 1.0 LogMAR postoperatively (p-value<0.001). Mean IOP decreased from 31.6 mmHg to 13.0 mmHg (p-value<0.001). Postoperative complications occurred in 36% of cases, most commonly posterior capsular rupture, posterior capsular opacification, and uveitis. Conclusions Phacomorphic glaucoma predominantly affects elderly individuals from rural and socioeconomically deprived backgrounds. Cataract surgery effectively reduces IOP and improves visual acuity; however, delayed presentation often limits visual recovery due to irreversible optic nerve damage. Early detection, community awareness, and timely surgical intervention are essential to prevent avoidable blindness from lens-induced glaucoma.